(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Phraseological units can be classified according to their various features from the point of view modern linguistics. Phraseological units are divided into categories according to their etymological, structural-semantic, motivational level meaning, accordingly, which word group they are represented by in linguistic works. The fund of Uzbek phraseology is replete with national and borrowed, terminological and non-terminological units as phraseology in English language.